Peran Dinas Sosial dalam Menangani Orang Dengan Gangguan Jiwa di Kabupaten Batang - Retno Setianingrum; Wihda Maulani (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
Mental disorders are serious problems that require special attention, especially for those who are neglected and do not receive adequate care. This study aims to see the role of the Batang Regency Social Service in handling People with Mental Disorders (ODGJ). This study uses qualitative methods with interview, observation, and documentation techniques to collect data. This study uses the role theory of Ilyas Yusuf (2014:05) with research variables including the role of the government as a Regulator, Facilitator, and Dynamicator. The results of the study stated that the role of the government as a regulator, the Batang Regency Social Service sets rules and policies related to handling People with Mental Disorders (ODGJ). Then the role of the government as a facilitator, they provide services and facilities that support rehabilitation and recovery, including access to health services and skills training, and the role of the government as a dynamicator, they work together with various parties and the community to increase awareness and involvement in supporting the handling of People with Mental Disorders (ODGJ). This study is expected to be a reference for local government policies and be useful for the community in dealing with mental health problems in Batang Regency.